If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 40 = 90 Reorder the terms: 40 + 8x = 90 Solving 40 + 8x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 8x = 90 + -40 Combine like terms: 40 + -40 = 0 0 + 8x = 90 + -40 8x = 90 + -40 Combine like terms: 90 + -40 = 50 8x = 50 Divide each side by '8'. x = 6.25 Simplifying x = 6.25
| -9(6f-3)= | | 13c-90=5c-34 | | 8/24=6/n | | 7.6(x-2.25)=-15.2 | | 6(10-5x)=45-5(5x+1) | | 64x^2+16x=1 | | 5m-20=4m+16 | | -9(7y-2)= | | 2-3a=8-2(2a+7) | | 2x+3+(2y-2)yi=0 | | 20=2w+4 | | 5.2(x-2.25)=-20.4 | | 18=2h-4 | | 54=-9a | | 4z+2=6z | | 12x^2+2x=5 | | 3(4-c)=-4(c-6) | | -8=a/-10 | | 4.375=7/8(b-4) | | -8=s/-10 | | (2a+9)(5a-6)=0 | | -5-4(6+7y)= | | 4x-(-2)-7x+12=5 | | -6x+21.4=2.2 | | 5n=3n+27 | | 100=p/10 | | -(4y+3)-(-3y-7)=1 | | (8h-1)(2h-3)=0 | | 3w+3=5w+7 | | 103.5=9(m+3.7) | | (4n+3)(n+9)=0 | | b+b+b+22=b+b+6 |